Crystal entrainment from cool, low-silica rocks into hot, high-silica melts: diverse primary melt compositions at Taranaki volcano, New Zealand - D'Mello N; Zellmer G; Kereszturi G; Ubide T; Procter J; Stewart R (The Geological Society of London, 2023)
The prevalence of antecrysts in arc volcanic rocks is widely accepted, yet the origin of their carrier melts remains debated. Crystal cargo in lava flows from Taranaki volcano, New Zealand, is dominated by plagioclase, clinopyroxene and amphibole. Except for some crystal rims, mineral phases are in disequilibrium with the melt they are entrained in. Major element chemistry reveals an almost complete compositional overlap between the crystals in the lava and those in xenoliths. The large volume fraction of crystals (35–55 vol%) exerts a strong control on whole-rock compositions, reducing silica by 5–11 wt% compared with the carrier melt. Yet there is no clear relationship between mineral proportion and bulk-rock compositions. Our data are inconsistent with extensive fractional crystallization, commonly invoked as a driver of magma evolution towards silica-rich compositions. Instead, high-temperature, aphyric carrier melts with varied compositions (55–68 wt% SiO2) entrain crystal cargo while ascending through colder, low-silica rocks. Thus, some parental melts at Taranaki volcano are significantly more silica-rich than arc basalts commonly invoked as primary magmas. Further, thermometric and hygrometric constraints preclude a deep crustal hot zone for the source of these melts, which we argue are of subcrustal origin.